2018
DOI: 10.1038/s41419-018-0877-2
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1-SOX9 axis-inducible COL10A1 promotes invasion and metastasis in gastric cancer via epithelial-to-mesenchymal transition

Abstract: Molecular biomarkers that predict disease progression might promote drug development and therapeutic strategies in aggressive cancers, such as gastric cancer (GC). High-throughput mRNA sequencing (RNA-seq) revealed that collagen type X alpha 1 (COL10A1) is a disease progression-associated gene. Analysis of 103 GC patients showed that high COL10A1 mRNA expression was associated with GC metastasis and reduced survival. We analyzed the COL10A1 promoter using the UCSC genome website and JASPAR database, and we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 54 publications
5
124
0
Order By: Relevance
“…GSEA analysis revealed the function of COL10A1 enriched in TGF-β signaling pathway in breast cancer. The previous study elucidated the mechanistic link between COL10A1 and the TGF-β1-SOX9 axis in gastric cancer progression [8]. Our study is the first to reveal the potential function between COL10A1 and TGF-β signaling pathway in breast cancer.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…GSEA analysis revealed the function of COL10A1 enriched in TGF-β signaling pathway in breast cancer. The previous study elucidated the mechanistic link between COL10A1 and the TGF-β1-SOX9 axis in gastric cancer progression [8]. Our study is the first to reveal the potential function between COL10A1 and TGF-β signaling pathway in breast cancer.…”
Section: Discussionmentioning
confidence: 60%
“…Collagen type X alpha 1 (COL10A1), a secreted, short-chain collagen, belongs to the collagen family, which is a major interstitial matrix component [5]. COL10A1 expression is elevated in many solid tumor types, such as colon cancer, esophagus cancer, and breast cancer, and displays vital roles in many critical cellular processes such as cell proliferation, migration, invasion and tumor vasculature [6][7][8]. COL10A1 protein levels in plasma might be a potential diagnostic predictor for early breast cancer [9].…”
Section: Introductionmentioning
confidence: 99%
“…Modularization can simplify the complex network into several modules for further research, and cores in the modules may have important functions. Several studies have shown that the core genes of the modules, such as COL1A1 and COL10A, participate in the invasion and [45][46][47] Thrombospondin 2 (THBS2) has also been reported to inhibit tumor growth and angiogenesis and has been recommended as a potential diagnostic biomarker for several types of cancer. 48,49 In addition, karyopherin subunit alpha 2 (KPNA2) is associated with cell proliferation, migration, and apoptosis, and has been found upregulated in many cancers and is an indicator of a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional therapeutic methods for gastric cancer are target-specific drug treatment (3), surgical excision (4), radiotherapy or chemotherapy (5). After surgery, the recurrence and metastasis of gastric cancer are pressing issues, and are complicated processes involved a series of events (6,7), such as tumor heterogeneity, and epigenetic changes (8,9). It has been confirmed that circulating tumour cells with the ability to diffuse and metastasize are a prime prognostic marker for cancer recurrence (10,11).…”
Section: Significantly Inhibited the Proliferation Of Ags And Hg-27 Cmentioning
confidence: 99%